The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1097/00006250-199203000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral-Umbilical Doppler Ratio As a Predictor of Adverse Perinatal Outcome

Abstract: Using a 3.5-MHz duplex Doppler system, 45 normal-growth and 45 growth-retarded fetuses were studied between 30-41 weeks' gestation. Velocity recordings were obtained from the middle cerebral artery and umbilical artery to calculate the ratio between the two pulsatility indexes. The cerebral-umbilical Doppler ratio is usually constant during the last 10 weeks of gestation. Therefore, a single cutoff value (1.08) was used, above which velocimetry was considered normal and below which it was considered abnormal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
350
7
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(412 citation statements)
references
References 0 publications
40
350
7
7
Order By: Relevance
“…Cerebroumbilical PI ratio was proposed by Gramellini et al and he suggeted that MCA/umbilical PI ratio had higher diagnostic accuracy and sensitivity in detecting IUGR (70%) and adverse perinatal outcome (90%) as compared to individual PI of umbilical and middle cerebral artery. 4 Similar to our findings, Ozeren et al also found that though cerebroumbilical PI ratio was higher in patients with preeclampsia, but had a lower sensitivity and diagnostic accuracy to predict adverse perinatal outcome. 11 Lakhar et al also found that umbilical artery PI is more sensitive than cerebroumbilical PI ratio in predicting adverse perinatal outcome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cerebroumbilical PI ratio was proposed by Gramellini et al and he suggeted that MCA/umbilical PI ratio had higher diagnostic accuracy and sensitivity in detecting IUGR (70%) and adverse perinatal outcome (90%) as compared to individual PI of umbilical and middle cerebral artery. 4 Similar to our findings, Ozeren et al also found that though cerebroumbilical PI ratio was higher in patients with preeclampsia, but had a lower sensitivity and diagnostic accuracy to predict adverse perinatal outcome. 11 Lakhar et al also found that umbilical artery PI is more sensitive than cerebroumbilical PI ratio in predicting adverse perinatal outcome.…”
Section: Discussionsupporting
confidence: 91%
“…In this study C/U PI ratio < 1.08 was taken as abnormal and predicted adverse perinatal outcome with 90% accuracy as compared to MCA PI or UA PI alone. 4 Bano S et al also in a recent study stressed that C/U PI ratio is a better predictor for adverse perinatal outcome. Apart from MCA-PI, MCA-PSV (peak systolic velocity) also holds promise.…”
Section: Introductionmentioning
confidence: 93%
“…Fetal brain sparing (low MCA PI or CPR) has been associated with adverse pregnancy outcomes, even in fetuses with normal umbilical artery Doppler [45,49]. However, the CPR improves the prediction of adverse pregnancy outcomes when compared to its individual components [49][50][51][52][53]. It has been shown that a suboptimal or low CPR is associated with short-term markers of neonatal outcome such as cord blood acidemia, need for emergency operative delivery and neonatal unit admission [54][55][56][57], as well as stillbirth and neonatal morbidity [48,[57][58][59].…”
Section: Fetal Dopplermentioning
confidence: 99%
“…Many studies (19,(21)(22)(23)(24) have confirmed that this parameter has a high sensitivity and specificity in detection of fetal blood flow redistribution and prediction of fetal hypoxia in growth-restricted human fetuses. It has been shown that the sensitivity of the C/U ratio in the prediction of perinatal outcome exceeds the sensitivity of cerebral resistance or UA RI alone, even in pregnancies complicated by only moderate hypoxia (21,22).…”
Section: Introductionmentioning
confidence: 98%